Implementasi Nilai Spiritual dalam Pengajaran Pendidikan Agama Islam Melalui Pengembangan Kecerdasan Spiritual - Moh. Fauzan; Ramdanil Mubarok (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2024)
This research aims to describe students' spiritual values, explore PAI teachers' strategies for developing spiritual values, and identify the challenges faced in developing spiritual values ​​at Al Munawwir South Sangatta Middle School. The research method used is descriptive qualitative with data collection through interviews, observation and documentation in the school environment. The research results show that students at Al Munawwir Sangatta Selatan Middle School show good spiritual intelligence through polite behaviour, discipline, and enthusiasm for religious learning. PAI teachers play an important role as motivators and role models in developing students' spiritual intelligence, using strategies such as positive habits, lectures and competitions. However, there are challenges such as lack of time and curriculum pressures that limit in-depth spiritual development. This research makes a new contribution to the literature by highlighting the need for a comprehensive approach to integrating spiritual values ​​into the PAI curriculum. Practical implications include the need for more support for teachers in developing innovative strategies that can increase students' spiritual intelligence in schools.